Substrate characteristics controls fungal denitrification and nitrous oxide emissions in an acidic upland soil - Guiping Ye; Zongsheng Yuan; Konglin Zhou; Chen Liang; Dan Wang; Wenbin Zhang; Luyuan Sun; Xiangying Wei; Yongxin Lin (Applied Soil Ecology, 2026)

Combined effects of Chlorella application and reduced nitrogen fertilization on nitrogen use efficiency and crop yield in facility vegetable systems - Guoliang Zhao; Jingyu Sun; Xingcheng Hu; Zhengxi Cai; Chen Li; Qingfeng Chen (Applied Soil Ecology, 2026)

Mechanism analysis and monitoring early warning of rainfall-induced instability for layered colluvial soil highway slopes - Jin Zhang; Jiale Yang; Zihan Ma; Xiangyu Zhang; Zhigang Tao; Chen Liu (Bulletin of Engineering Geology and the Environment, 2026)

Cultural expression through art in alzheimer’s disease: a psychological analysis of painting-based engagement, identity, meaning-making, and affective regulation - Yi Guo; Houjun Ying; Wei Wang; Hanchen Li; Gaoming Jia; Rushana Sulaiman (Acta Neurologica Belgica, 2026)

Peripheral CD4 T-Cell State Remodeling in Migraine Revealed by Single-Cell RNA Sequencing - Quan Feng; Yichen Li; Na Li; Weisheng Zhan; Ge Tan (Journal of Molecular Neuroscience, 2026)

Sea Cucumber Neuropeptides: Bridging Molecular Insights Towards Aquaculture Innovations - Yingqiu Zheng; Huachen Liu; Saowaros Suwansa‐ard; Scott F. Cummins; Muyan Chen (Reviews in Aquaculture, 2026)
The sea cucumber (class Holothuroidea) holds significant commercial value due to strong global demand, especially in East and Southeast Asian markets. Overexploitation of wild stocks has thus driven aquaculture expansion; however, current culture methods remain inadequate to meet projected demand or overcome traditional practice limitations. As evolutionarily ancient endogenous bioactive molecules, neuropeptides regulate diverse physiological processes and behaviors, demonstrating great potential as eco‐friendly tools for precision sea cucumber aquaculture. Identification and functional characterization of these neuropeptides improve our understanding of their evolutionary history and facilitate their application in aquaculture practice. In this review, we summarize the diversity of known sea cucumber neuropeptides and their receptors, their engagement with downstream cellular signaling pathways, and their roles in key biological processes, including feeding and growth, reproduction, regeneration, larvae settlement and metamorphosis, and locomotion. Future research should prioritize investigating neuropeptide regulatory networks, determining their functions across developmental stages, developing large‐scale peptide production methods, and improving delivery efficiency, all of which are critical for the application of neuropeptides to achieve sustainable, eco‐friendly sea cucumber aquaculture.

Wollastonite enhances microbial diversity and ecological network stability - Yanzhi Wang; Yongfeng Wang; Ronghua Kang; Chunjie Tian; Guochen Li; Feifei Zhu; Ang Wang; Geshere Abdisa Gurmesa; Chenxia Su; Chang Liu; Dong Liu; Zhi Quan; et al. (Applied Soil Ecology, 2026)

Nitrogen addition and expansion of Ligularia virgaurea drive decoupling between ammonia and nitrite oxidation - Miao Zhang; Anning Zhang; Zi Yang; Wanyu Xia; Xuanchen Liu; Xiaoxuan Jiang; Xia Zhao; Hanwen Cui; Guoliang Sha; Sa Xiao; Shuyan Chen; Beat Frey (Applied Soil Ecology, 2026)

Agricultural and socio-ecological benefits of reducing chemical nitrogen fertilizer and using organic amendments: a sugar beet case study in China's black soil region - Yunlong Guo; Xiaochen Lin; Muhammad Faheem Adil; Muhammad Ishfaq; Muhammad Riaz; Shafaque Sehar; Songlin Yang; Yan Wang; Zhishan Yan; Baiquan Song (Applied Soil Ecology, 2026)

Vermicompost-mediated suppression of root-knot nematodes relates to tomato root bacterial community composition under greenhouse conditions - Chen Liang; Leixin Yu; Qinghai Yang; Lijuan Yang; Chuang Yang; Xuguang Niu; Feiyu Dong; Diwen Yang (Applied Soil Ecology, 2026)

Research Progress on the Roles of Mitochondria and Mitophagy in Fish Innate Immunity - Yunli Zhang; Chen Li; Xianghui Kong (Reviews in Aquaculture, 2025)
Mitochondria, known as the energy powerhouses of cells, also have a significant role in the innate immune response. Consequently, maintaining mitochondrial homeostasis is crucial for overall organismal health. Mitochondrial quality is tightly regulated through processes such as mitochondrial dynamics and mitophagy. However, compared to mammals, the regulatory roles of mitochondria and mitophagy in fish immunity have been less extensively studied. This article provides a comprehensive review of mitochondrial quality control and mitophagy mechanisms, with a particular focus on summarizing the mitochondrial antiviral signaling (MAVS) pathway and its interactions with viruses in fish. Additionally, it explores the interplay between MAVS and innate immunity, the association between mitophagy and viral infections in fish, and how the regulation of mitophagy can promote fish health. By enhancing the understanding of the functions of mitochondria and mitophagy in fish immunity, this review offers valuable insights for disease prevention, control, and the sustainable development of fish populations.

Methane oxidation in alpine meadow and wetland soils on the Qinghai-Tibet Plateau: Roles of USCγ and conventional methanotrophs - Yan Tong; Jinchen Liu; Xiaomeng Zhu; Hongan Pan; Yongcui Deng (Applied Soil Ecology, 2025)

Cessation of manure application diminishes the dissemination potential of antibiotic resistance genes by altering bacterial interaction patterns in soil–lettuce systems - Ruochen Li; Xin Pei; Ming Zhang; Xuhui Deng; Chengyuan Tao; Jiabao Wang; Xueli Chen; Nicholas Clarke; Lidia Sas-Paszt; Zongzhuan Shen; Rong Li; Qirong Shen (Applied Soil Ecology, 2025)

Microbial inoculants drive disease suppression and rhizosphere modulation for effective management of pepper phytophthora blight - Muye Xiao; Xuchen Liu; Xiaozhong Wang; Wencai Lu; Tong Zhang; Yuheng Yang (Applied Soil Ecology, 2025)

Unraveling the role of pyrolysis temperature in biochar-mediated modulation of soil microbial communities and tobacco bacterial wilt disease - Shichen Li; Linyuan Yang; Tao Jiang; Waqar Ahmed; Fupeng Mei; Jinhao Zhang; Tao Zhang; Yingfen Yang; Xiaoci Peng; Qu Shan; Dexiang Luo; Zhengxiong Zhao (Applied Soil Ecology, 2025)

Responses of soil microbial community diversity and co-occurrence networks to interspecific interactions in soybean/maize and peanut/maize intercropping systems - Huai-Ying Ma; Surigaoge Surigaoge; Yi Xu; Yu-Chen Li; Peter Christie; Wei Ping Zhang; Long Li (Applied Soil Ecology, 2024)

Gaidai multimodal risk evaluation methodology based on cargo vessel onboard measurements, given structural damage accumulation - Oleg Gaidai; Alia Ashraf; Yu Cao; Jinlu Sheng; Hongchen Li; Zirui Liu; Yan Zhu (Discover Oceans, 2024)

Onboard multivariate hazard assessment for UIKKU chemical tanker by Gaidai reliability method - Oleg Gaidai; Alia Ashraf; Jinlu Sheng; Yan Zhu; Vladimir Yakimov; Hongchen Li; Zirui Liu; Yu Cao (Discover Oceans, 2024)

Autophagy regulation of virus infection in aquatic animals - Chen Li; Yunli Zhang; Xianliang Zhao; Li Li; Xianghui Kong (Reviews in Aquaculture, 2023)
Autophagy is a conserved intracellular degradation process that is required to maintain host homeostasis and cope with invading pathogens. Over the past few decades, studies on mammals have greatly increased our understanding of the relationship between autophagy and virus infection. Autophagy may convey the invader to lysosomes to degrade or activate the host immune response against virus replication. However, many viruses have developed some strategies that evade the degradative nature of autophagy or hijack this pathway for their gain. It follows that autophagy during viral infection is a double‐edged sword. In contrast to mammals, the review on autophagy modulated by the aquatic animal virus is limited. Here, after a brief description of the main information about autophagy, we highlight current progress on the interplays between autophagy and virus infection in aquatic animals, including the phenomenon of autophagy upon virus infection, the effect of modulating autophagy on virus replication, and the crosstalk between autophagy and immune response during virus infection. This review will help us better understand the pathogenic mechanism of aquatic animal viruses and develop proper antiviral countermeasures aimed at modulating autophagy.

The role of ferroptosis in fish inflammation - Feng Gao; Xiaowei Shi; Chao Pei; Xianliang Zhao; Lei Zhu; Jie Zhang; Li Li; Chen Li; Xianghui Kong (Reviews in Aquaculture, 2023)
Ferroptosis, as one of cell death modalities, is driven by iron‐dependent phospholipid peroxidation and regulated by various cellular metabolic pathways, including iron, amino acid and lipid metabolism, as well as disease‐related signalling pathways. Cell survival or death is a critical issue in the inflammatory response. On the one hand, ferroptosis is more immunogenic than apoptosis, and ruptured ferroptotic cells release damage‐associated molecular patterns (DAMPs), which can trigger an inflammatory response. On the other hand, various pathogenic bacteria may cause peroxidation of polyunsaturated fatty acids (PUFAs) on the cell membrane, leading to ferroptosis. In fish, the key genes and signalling pathways related to ferroptosis are conserved, but there are still differences among fish species. In recent years, frequent occurrences of fish diseases have posed a considerable challenge to the large‐scale aquaculture. The specific precursors for ferroptotic cell death were iron‐dependent oxidative stress and lipid peroxidation, which always occur in fish inflammation. This review summarizes recent studies on ferroptosis in fish inflammation, that is, iron‐dependent programmed cell death, to address ferroptosis, inflammation and correlations between them in fish. This review may contribute to a better understanding of the underlying mechanisms of ferroptosis and inflammation in fish and provides suggestions for sustainable development and large‐scale aquaculture farming.